2020
DOI: 10.1371/journal.pone.0235190
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of little change: An analysis of U.S. medical school basic science faculty by sex, race/ethnicity, and academic rank

Abstract: To examine changes in U.S. medical school basic science faculty over the last 20 years (1998-2018), we undertook an observational study utilizing data from the American Association of Medical Colleges Faculty Roster. Rank (Instructor, Assistant Professor, Associate Professor, and Professor), sex (Female), and race/ethnicity (Asian, Black or African American, Hispanic, Latino, Spanish Origin, or Multiple Race-Hispanic, and White) were analyzed; this reflected a population of 14,047 (1998) to 18,601 (2018) facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Citation metrics, which have been widely used across most research areas due to their quantitative nature and easy estimation, influence career advancement at all levels including graduate opportunities, funding success, career positions, awards, distinctions, and tenure and promotion. However, a lack of diversity among the most cited scientific authors is driven by historical demographics of faculty and those in academic leadership positions [13][14][15][16]. While there have been recent successes in increasing diversity among trainees and early-career researchers [8,9], differential recruitment, retention, and promotion rates with respect to age, sex, gender, race, and ethnicity continue to perpetuate the lack of diversity among all career levels of scientists [14,[17][18][19].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
“…Citation metrics, which have been widely used across most research areas due to their quantitative nature and easy estimation, influence career advancement at all levels including graduate opportunities, funding success, career positions, awards, distinctions, and tenure and promotion. However, a lack of diversity among the most cited scientific authors is driven by historical demographics of faculty and those in academic leadership positions [13][14][15][16]. While there have been recent successes in increasing diversity among trainees and early-career researchers [8,9], differential recruitment, retention, and promotion rates with respect to age, sex, gender, race, and ethnicity continue to perpetuate the lack of diversity among all career levels of scientists [14,[17][18][19].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
“…4,5 For example, less than 5% of all US medical school faculty are Black or Latinx, and only 35.3% are women. 6 Beyond representation, serious disparities in funding, career satisfaction, formal compensation, and other opportunities persist. 7,8 Black investigators are 10 percentage points less likely than white applicants to be awarded NIH research funding, even after controlling for educational background, research productivity, and employer characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the health services research workforce in the USA represents a multidisciplinary community of scholars with an expressed commitment to furthering equity in health care [3], many identities remain underrepresented in the ranks of academic medical centers and research institutions [4,5]. For example, less than 5% of all US medical school faculty are Black or Latinx, and only 35.3% are women [6]. Beyond representation, serious disparities in funding, career satisfaction, formal compensation, and other opportunities persist [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…With the acceptance of bias as a factor in research engagement, as it is found in so many other contexts, comes the ability to address it through education, resource allocation, and the diversification of the scientific workforce itself. 49 Certainly, we cannot conclude that there is "nothing we can do" nor can we exclude researchers working in predominantly White communities from obligations to collect data and conduct analysis on diverse samples. Our path forward is in facing barriers on both the researcher and community sides of the problem and developing new solutions and innovative approaches.…”
Section: Discussionmentioning
confidence: 99%